Scientific production of physical education in brazil: analysis of teacher´s production in the institution of formation in the state of Paraiba and Pernambuco - Tenorio Brasileiro, Lívia; do Amaral, Manoel Francisco; de Paiva, Andrea Carla (Universidad Pedagógica y Tecnológica de Colombia, 2014)
The study a constitutive part of the thematic project: Scientific production in the field of physical education in the northeast of Brazil: the impact of system of postgraduates’ students – southeast region, in the production of teachers’ masters and doctors in the implementation of investigations in the trainer institutions in the region. The project emerged in the research: epistemology of physical education: the scientific production in the field of physical education in the northeast states and it is found among the most important studies about production problems of education knowledge’. Objectives: to identify the researchers who are working in Pernambuco and Paraiba, To identify the production through the use of scientist matrixes which have been developed in the epistemology field, the thematic trends and theoretical – methodological, and the contributions of this production in the professional field and in the consolidation of research institutions. The study subject is there searchers who work in the high education and this will have as base the indicators about the postgraduate students system of the country in order to identify its impact in the northeast region where there are three courses: UPE/UFPB, UFRN y UFS. We use the information about four physical education courses (UFPE, UPE, UFPB, UEPB). The postgraduate teachers researchers were catalogued by: level, titled year, program, area, thematic, group, research line, research problem, objectives and type of investigation. The information gathering into the reading of master’s thesis and doctor program and other studios about the production conditions in postgrad studios was organized on base of production identification and characterization and on the production conditions and production characterization and its contribution to the professional formation.